Pengaruh latihan foot spedd ladder drill terhadap peningkatan kecepatan dan kelincahan pemain tim bola voli kalimantong - Yanza Deva Kirana; Soemardiawan; Kurnia Tuafik (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
So the problem in this study is where every open match and during training for the Kalimantong Volleyball Team players, lack of speed and agility training, causes players to lose a lot of balls when defending, and attacking in volleyball games is not good in terms of speed and agility. So it often causes defeat for the team. Research Objectives To find out whether there is an effect of foot spedd ladder drill training on increasing the speed of the Kalimantong Volleyball Team players. The research design used a two group pretest-posttest design. The research sample is all players of the Kalimantong Volleyball Team, totaling 12 people. The research sampling technique used population study research. The research instrument used a speed test with 30 meters and an agility test instrument using a shutel run. From the results of statistical data analysis, the effect of foot spedd ladder drill training on increasing the speed and agility of Kalimantong Volleyball Team players, so that the tcount value X1 (speed) is 4,293 and X2 (agility) is 2,643 values simultaneously between Y and X1 and X2 draws the conclusion of the analysis table at a significant level of 5% with the number of samples (n - 1) namely 11 of 1,796. So, looking at the results of the foot sped ladder drill exercise on the increase in speed from tcount > ttable (4,293 > 1,796), and the increase in speed from tcount > ttable (2,643 > 1,796), it can be concluded that